2021
DOI: 10.1080/10408444.2021.1939654
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of the human relevance of the mode of action for rodent liver tumor formation by activators of the constitutive androstane receptor (CAR)

Abstract: Many nongenotoxic chemicals have been shown to produce liver tumors in mice and/or rats by a mode of action (MOA) involving activation of the constitutive androstane receptor (CAR). Studies with phenobarbital (PB) and other compounds have identified the key events for this MOA: CAR activation; increased hepatocellular proliferation; altered foci formation; and ultimately the development of adenomas/carcinomas. In terms of human relevance, the pivotal species difference is that CAR activators are mitogenic agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 184 publications
(350 reference statements)
0
5
0
Order By: Relevance
“…In the mammalian liver, numerous chemicals activate nuclear receptors such as the CAR, pregnane X receptor (PXR) [14,15,46,47], or PPARα [16,17,48]. Activation triggers a proliferative stimulus in rodents to the hepatocyte, leading to the production of more hepatocytes.…”
Section: Target Organs and Target Cell Types: Some Case Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mammalian liver, numerous chemicals activate nuclear receptors such as the CAR, pregnane X receptor (PXR) [14,15,46,47], or PPARα [16,17,48]. Activation triggers a proliferative stimulus in rodents to the hepatocyte, leading to the production of more hepatocytes.…”
Section: Target Organs and Target Cell Types: Some Case Examplesmentioning
confidence: 99%
“…This leads to an accumulation of cells, and (as the total number is higher at the start of the next cell replication cycle) providing more opportunities for spontaneous errors even if the rate of cell proliferation is the same as that of controls. There are specific examples of decreased cell death possibly contributing to increases in cell number, for example, some evidence in animal models exposed to nuclear receptor activators [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al 14 also demonstrated the phenobarbital mediated activation of CAR and murine CAR ligand 1,4-bis-[2-(3,5,-dichloropyridyloxy)] benzene (TCPOBOP) for murine liver tumorigenesis. 9,36,41 Several studies in the recent years have indicated the involvement of key signaling pathways Wnt/B catenin and Hippo/YAP in CAR-mediated hepatocellular carcinogenesis. CAR induction likely activates both signaling pathways synergistically leading to CAR-mediated liver cancer development.…”
Section: Nuclear Receptor Moa-induced Hepatocarcinogenesis: Human Rel...mentioning
confidence: 99%
“…Human relevance of liver tumorigenesis by PB and other activators of CAR is controversially discussed (Braeuning et al 2015;Braeuning and Schwarz 2016;Elcombe et al 2014;Yamada et al 2015). While the activation of CAR in humans by PB is generally accepted, the fact that PB induces hepatocellular proliferation in mouse liver but not in cultured human hepatocytes in vitro (Haines et al 2018;Parzefall et al 1991;Plummer et al 2019) has often been put forward as a key argument against human relevance of CAR-mediated nongenotoxic carcinogenesis in humans (Elcombe et al 2014;Lake 2018;Yamada et al 2021).…”
Section: Introductionmentioning
confidence: 99%